A study of various cesarean section techniques at a government tertiary care centre: Misgav Ladach cesarean section versus Pfannenstiel cesarean section - Kanani, Medha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: It is important to examine every step in any surgery to identify and evaluate its imortance, necessity and purpose with a view to find its better alternatives if they can be found at all. The most appropriate surgical procedure is the one which takes minimum time to be complete, simplest to perform, causing least damage and least complication for the patient. Present study was undertaken to assess the benefits of the Misgav Ladach cesarean section technique in comparison to the conventional Pfannenstiel technique in the tertiary care hospital and evaluate the operative parameters like efficacy, safety, duration of surgery, blood loss, need for suture material, post-operative pain and post-operative stay in hospital. Methods: All the women posted for emergency cesarean section in the Obstetrics OT at Sir T Hospital, Bhavnagar, Gujarat were included in this study. Some of the common indications at our hospital for cesarean section were fetal distress, cephalopelvic disproportion, failure of progress of labour, breech presentation, previous cesarean section and failed induction. Informed consent was taken. All the patients were randomly allocated to two groups with 50 women in each group. Group 1 Pfannenstiel incision and Group 2 Misgav Ladach. Results: The duration of surgery, blood loss and post-operative pain were significantly less in the Misgav Ladach group (P<0.001). Conclusions: Misgav Ladach technique of cesarean section has many advantages and should be used routinely.